KARAKTER ARSIP SULTAN TERNATE KOLEKSI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA (The Characteristics of Sultan Ternate’s Manuscripts Collection National Library 0f Indonesia) - Priscila Fitriasih Limbong (Balai Bahasa Sulawesi Selatan, 2019)
National Library of Indonesia has more than 11.000 ancientmanuscripts in their collection. The manuscript collection is devided into two groups, which are bounded book manuscript collection and non-book collection that is stored inside achest. Bounded book manuscript collection is seperated into 17 sub-collections that have quite clear identity and history while chest manuscriptis separated into 37 sub-collections (one of the collections is Sultan Ternate archives) that does not have clear origin and collection characteristics. Related to that, this article will be discussing the characteristics of Sultan Ternate’s archives chest manuscript collection. The discussion about this problem had to be done in order to give a clear and comprehensive description about the content and characteristics of the Sultan Ternate’s archive collection. The description of the characteristics of Sultan Ternate’s archive collection can be beneficialas research data for many studies, especially the one that is related to historical science and codicology.AbstrakPerpustakaan Nasional Republik Indonesia (selanjutnya disebut PNRI) memiliki koleksi naskah kuno sebanyaklebih dari 11.000 naskah. Koleksi naskah tersebut dibagi menjadi dua kelompok besar, yaitu koleksi naskah buku berjilid dan koleksi nonbuku yang tersimpan di dalam peti. Koleksi naskah buku berjilid terbagi atas 17 subkoleksi yang cukup jelas identitas dan sejarahnya, sedangkan naskah peti terbagi atas 37 subkoleksi (antara lain koleksi arsip Sultan Ternate) yang kurang jelas asal muasal dan ciri koleksinya. Sehubungan dengan itu, makalah ini membahas karakteristik koleksi naskah peti arsip Sultan Ternate. Pembahasan masalah ini perlu dilakukan untuk memberikan gambaran yang jelas dan komprehensif tentang isi dan ciri-ciri koleksi arsip Sultan Ternate. Gambaran tentang karakteristik koleksi arsip Sultan Ternate ini dapat dijadikan data penelitian bagi kajian berbagai disiplin ilmu, terutama yang terkait dengan bidang ilmu sejarah dan kodikologi.